"Maybe English first and then Balinese and Bahasa Indonesia": A case of language shift, attrition, and preference - Siana Linda Bonafix; Christine Manara (Indonesian JELT, 2016)
This small-scale qualitative study aims to explore the participants’ view of languages acquired, learned, and used in their family in an Indonesian context. The two participants were Indonesians who came from multilingual and mixed-cultural family background. The study explores three research questions: 1) What are the languages acquired (by the participants’ family members), co-existed, and/or shift in the family of the two speakers? 2) What factors affect the dynamicity of these languages? 3) How do the participants perceive their self-identity? The qualitative data were collected using semi-structured and in-depth interviews. The interviews were audio-taped and transcribed to be analyzed using thematic analysis. The study detects local language shift to Indonesian from one generation to the next in the participants’ family. The data also shows several factors for valorizing particular languages than the others. These factors include socioeconomic factor, education, frequency of contact, areas of upbringing (rural or urban) and attitude towards the language. The study also reveals that both participants identify their self-identity based on the place where they were born and grew up instead of their linguistic identity.